BRASSINAZOLE RESISTANT 1 Mediates Brassinosteroid-Induced Calvin Cycle to Promote Photosynthesis in Tomato - Yin, Xiaowei; Tang, Mingjia; Xia, Xiaojian; Yu, Jingquan (Frontiers in Plant Science, 2022)
Calvin cycle is a sequence of enzymatic reactions that assimilate atmospheric CO2 in photosynthesis. Multiple components are known to participate in the induction or suppression of Calvin cycle but the mechanism of its regulation by phytohormones is still unclear. Brassinosteroids (BRs) are steroid phytohormones that promote photosynthesis and crop yields. Here, we study the role of BRs in regulating Calvin cycle genes to further understand the regulation of Calvin cycle by phytohormones in tomato. BRs and their signal effector BRASSINAZOLE RESISTANT 1 (BZR1) can enhance the Calvin cycle activity and improve the photosynthetic ability. BRs increased the accumulation of dephosphorylated form of BZR1 by 94%, and induced a 88%-126% increase in the transcription of key genes in Calvin cycle FBA1, RCA1, FBP5 and PGK1. BZR1 activated the transcription of these Calvin cycle genes by directly binding to their promoters. Moreover, silencing these Calvin cycle genes impaired 24-epibrassinolide (EBR)-induced enhancement of photosynthetic rate, quantum efficiency of PSII as well as Vc,max and Jmax. Taken together, these results strongly suggest that BRs regulate Calvin cycle in a BZR1-dependent manner in tomato. BRs that mediate coordinated regulation of photosynthetic genes are potential targets for increasing crop yields.